Material and wave relaxation phenomena effects on the rheology of Maxwell nanofluids - Ahmed, Awais; Alhowaity, Sawsan; Ghoneim, Mohamed E.; Gamaoun, Fehmi; Tag-eldin, Elsayed; Yassen, Mansour F.; Sarfraz, Mahnoor (Frontiers in Physics, 2022)
This study analyzed thermal and mass transport in magnetohydrodynamic Maxwell nanofluids over a cylinder stretched along the z-direction. The Cattaneo-Christov diffusion theory and Buongiorno’s model were employed to model the problem. The influences of Joule heating, chemical reaction rate, and heat generation were also considered. Appropriate similar variables were utilized to transform the constitutive equations. A semi-analytical method, namely the homotopy analysis method (HAM) in Wolfram Mathematica, was used to compute the problem solution. The results demonstrated the inverse variation in flow behavior with increased Maxwell parameter values; however, thermal and solutal transport displays the opposite trend. Additionally, the flow field showed resistance due to the presence of the magnetic field, while Joule heating enhanced the energy and mass transport phenomena. The results regarding the coefficient of skin friction along the radial direction are consistent with values reported in the literature.